2003
DOI: 10.1111/1540-6261.00555
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic Risk Matters!

Abstract: This paper takes a new look at the predictability of stock market returns with risk measures. We ¢nd a signi¢cant positive relation between average stock variance (largely idiosyncratic) and the return on the market. In contrast, the variance of the market has no forecasting power for the market return. These relations persist after we control for macroeconomic variables known to forecast the stock market. The evidence is consistent with models of timevarying risk premia based on background risk and investor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
437
9
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 965 publications
(482 citation statements)
references
References 101 publications
33
437
9
3
Order By: Relevance
“…Some studies (Bali et al (2005), Huang et al (2010), among others) suggest idiosyncratic risk is not priced. In other studies, both negative (Ang, et al (2006), Guo and Savickas (2010) and positive relations (Goyal and Santa-Clara (2003), Diavatopoulos, Doran, and Peterson (2008), Malkiel andXu (2006), Fu (2009)) are documented. In a recent study, Fu (2009) demonstrates that the commonly used ordinary least square (OLS) method may not be appropriate to calculate idiosyncratic risk since idiosyncratic volatility does not follow a random walk.…”
Section: Introductionmentioning
confidence: 80%
“…Some studies (Bali et al (2005), Huang et al (2010), among others) suggest idiosyncratic risk is not priced. In other studies, both negative (Ang, et al (2006), Guo and Savickas (2010) and positive relations (Goyal and Santa-Clara (2003), Diavatopoulos, Doran, and Peterson (2008), Malkiel andXu (2006), Fu (2009)) are documented. In a recent study, Fu (2009) demonstrates that the commonly used ordinary least square (OLS) method may not be appropriate to calculate idiosyncratic risk since idiosyncratic volatility does not follow a random walk.…”
Section: Introductionmentioning
confidence: 80%
“…Their empirical evidence suggests that idiosyncratic risk commands a positive risk premium. Goyal and Santa-Clara (2003) claimed that the average stock variance is positively related to market returns, but Ang et al (2009) showed that stocks with high idiosyncratic risk deliver abysmally low returns. Guo and Savickas (2008) and Kearney and Poti (2008) found that market returns are positively related to lagged market variance and negatively related to lagged idiosyncratic variance in US.…”
Section: Introductionmentioning
confidence: 99%
“…This is to say that the variance of a security includes both systematic and specific portion of risk, the sum also known as "Total Risk" (Elton et al, 2003;Goyal and Santa Clara, 2003). Both measures are well established in the finance literature with higher values corresponding to riskier securities.…”
Section: Variable Measurementmentioning
confidence: 99%